2008
DOI: 10.2134/agronj2008.0060
|View full text |Cite
|
Sign up to set email alerts
|

How Well Does Zone Sampling Based on Soil Electrical Conductivity Maps Represent Soil Variability?

Abstract: In zone soil sampling a field is divided into homogenous areas using an easy to measure ancillary attribute (e.g., apparent soil electrical conductivity [ECa]) and a few samples are taken from each zone to estimate the soil characteristics in each zone. This study determined if ECa–directed zone sampling in two fields in northeastern Colorado could correctly predict soil texture and soil organic matter (SOM) patterns of samples taken by a more intensive grid sample method. Each field, which were predominantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…When the farmers were confronted with the data, they noted that the data did not always express the differences as they observed them. Shaner et al (2008) reported that if something differs little but is statistically significant, it is probably not of agronomic importance. This study has shown it may well be the other way round, with statistical testing being less sensitive than the farmer who has observed the agronomic importance over several years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When the farmers were confronted with the data, they noted that the data did not always express the differences as they observed them. Shaner et al (2008) reported that if something differs little but is statistically significant, it is probably not of agronomic importance. This study has shown it may well be the other way round, with statistical testing being less sensitive than the farmer who has observed the agronomic importance over several years.…”
Section: Discussionmentioning
confidence: 99%
“…The budget allowed two fields of the last farmer interviewed to be sampled. To avoid boundary effects (Fleming et al 2000;Shaner et al 2008), farmers in this study were asked to indicate what buffer they would like to use near zone boundaries. In addition, parts of the field that were not of interest to the farmer, such as headlands, could be left out of the sampling scheme on the indication of the farmer.…”
Section: Interviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…At field and landscape scales, EC a maps have the potential to provide higher levels of resolution and greater distinction of soil types than soil maps prepared with traditional tools and survey methods provided there is significant variation in at least one of the factors that affects soil EC a (James et al, 2003;Jaynes, 1995Jaynes, , 1996aShaner et al, 2008). However, EC a surveys can also be used to confirm highly uniform soil properties throughout a field .…”
Section: Refine and Improve The Quality Of Soil Mapsmentioning
confidence: 99%
“…Thigpen (2007) applied PA principles to golf courses in the Carolinas (USA) for site-specific application of fertilizers using grid sampling (about 70 soil samples per fairway on a 15-20 m grid) and digital mapping of the data, but this is costly as each soil sample is analyzed separately. Shaner et al (2008) found that SSMU based soil sampling in agricultural fields was a viable option to grid sampling provided the soil sample locations were selected using appropriate protocols, such as those suggested by Corwin and Lesch (2005b). With SSMUs, there are several ways to reduce costs for site-specific application of fertilizers and amendments in PTM, such as:…”
Section: Salinity Managementmentioning
confidence: 99%